ANALISIS BIOEKONOMI DAN POTENSI LESTARI IKAN CAKALANG DI PROVINSI ACEH - Cut Putri Mellita Sari; Nurainun Nurainun (LPPM Universitas Malikussaleh - Indonesia, 2022)
The purpose of this study is to provide an overview of the level of utilization of fishery resources in an area and can be carried out in a sustainable manner. The method used in analyzing the level of utilization of fishery resources is through CPUE, MSY and profit. Base on the research, in the 2016-2021 research period, JTB < MSY was obtained, which means that fishing effort has not exceeded the limit of sustainable stocks in the waters, so that fishing effort is increased to get maximum results but still based on the calculated MSY limit. The estimated average profit per year that can be obtained in fishery management is Rp. 724,032,170.5 so that it is feasible to do fisheries management economically